2(x+3)-3(x-1)=3+2x

Simple and best practice solution for 2(x+3)-3(x-1)=3+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+3)-3(x-1)=3+2x equation:


Simplifying
2(x + 3) + -3(x + -1) = 3 + 2x

Reorder the terms:
2(3 + x) + -3(x + -1) = 3 + 2x
(3 * 2 + x * 2) + -3(x + -1) = 3 + 2x
(6 + 2x) + -3(x + -1) = 3 + 2x

Reorder the terms:
6 + 2x + -3(-1 + x) = 3 + 2x
6 + 2x + (-1 * -3 + x * -3) = 3 + 2x
6 + 2x + (3 + -3x) = 3 + 2x

Reorder the terms:
6 + 3 + 2x + -3x = 3 + 2x

Combine like terms: 6 + 3 = 9
9 + 2x + -3x = 3 + 2x

Combine like terms: 2x + -3x = -1x
9 + -1x = 3 + 2x

Solving
9 + -1x = 3 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
9 + -1x + -2x = 3 + 2x + -2x

Combine like terms: -1x + -2x = -3x
9 + -3x = 3 + 2x + -2x

Combine like terms: 2x + -2x = 0
9 + -3x = 3 + 0
9 + -3x = 3

Add '-9' to each side of the equation.
9 + -9 + -3x = 3 + -9

Combine like terms: 9 + -9 = 0
0 + -3x = 3 + -9
-3x = 3 + -9

Combine like terms: 3 + -9 = -6
-3x = -6

Divide each side by '-3'.
x = 2

Simplifying
x = 2

See similar equations:

| x=98-12(9x+1) | | 6x^2-16x-6= | | X^2(x-6)=4(2-3x) | | -18+4p=3(1-p) | | 4(x+3)=3x+5 | | 6a+6=36 | | X^3-6x^2-8+12x=0 | | -16(t^2-8t-240)=0 | | 0.3x=4.5 | | t^2-8t-240=0 | | 0.16(y-6)+0.18y=0.04y-0.03(40) | | 6x-5=6(x+7) | | X^2+14x=7 | | 5x-6=18-2x | | 16+5x=12+3x | | 78+2x=360 | | -4(1+7n)=-6n+7 | | 6-(3z-2)=5-4z | | 17x-(4x-2)=15 | | 5n-n+5=2n-7 | | 5x-7x+21=4x+39 | | -5n-2(-3-8n)=28+3n | | 21=x/18 | | 8x+3x-2x=21+6 | | -144=-12+11m | | 8y-7=15y+7 | | -6(3z-2)=5-4z | | -2x=-60 | | a=46 | | 3x+6=81 | | -2y-15=-5 | | -9(x-3)=-4(x+3)-2x |

Equations solver categories